On Strong Forms of Generalized Closed Sets in Micro Topological Spaces - R. Bhavani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we introduce different types of Micro generalized closed sets in Micro topological spaces and their properties. Also we introduce a new class of sets namely Micro-– closed sets in Micro topological spaces and this is another generalization of closed sets and proved that the class of Micro- – closed sets.